Health Care Reform Controlling Spending and Increasing Efficiency - Oxley, Howard (OECD Publishing, 1994)
The paper reviews trends in health-care expenditure and assesses the main forces underlying the increase since 1960. It then describes and evaluates various health-care reforms. The report argues that top-down budget controls appear to have had some success in reducing the growth in health-care spending but, to be sustainable, they need to be supported by microeconomic reforms. Significant improvements in micro-efficiency and effectiveness can be obtained by improving incentives facing health-care providers. Policy developments in a few leading countries suggest that a system where funders/insurers act as purchasers, contracting with competing health-care providers, is a promising model for reform. A statistical annex assesses whether differences in institutional arrangements for funding and providing health care explain international differences in health expenditure ...
Keywords: Economics